Penerapan Kompres Hangat Jahe Merah Pada Asuhan Keperawatan Gerontik Klien Gout Arthritis Dengan Masalah Keperawatan Nyeri Akut Di Puskesmas Wongsorejo (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Gout Arthritis is joint inflammation caused by increased uric acid levels in the blood due to purine metabolism distribution (hyperuricemia) in the body, characterized by joint pain that can interfere with the patient's activities. One of the non–pharmacological treatments that can be used for Gout Arthritis is red ginger warm compresses, often used to treat joint inflammation. This scientific paper aims to determine the effect of warm red ginger compress on changes in the pain scale in Gout Arthritis patients in Wongsorejo village. The method was a case study of implementing nursing care and applying Evidence-Based Nursing (EBN). From the assessment, the main diagnosis was acute pain. Red Ginger Warm Compress was given once a day by giving 2 segments of ginger or 9 grams, placing it in the area experiencing joint pain for 10 minutes and then doing a pain assessment again with the Numerical Tw`ig Scale (NRS). The results of the case study in the two respondents after seven days was a decrease in the pain scale from 8 and 6 and after the treatment the pain can be reduced to scale 1 in pain. Red ginger warm compresses are an effective complementary therapy for reducing pain in Gout Arthritis patients. It is recommended that nurses can apply Red Ginger Warm compress to reduce pain in Gout Arthritis clients.